(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2022)
The concept of happiness is an equally important topic of discussion in both Islamic and Western philosophy. This article presents a comparative analysis of happiness concepts from Islamic as well as Western points of view. The article aims at discovering the influence of al-Ghazali (a medieval Muslim scholar of Sufi persuasion) upon Syed Muhammad Naquib al-Attas, a present-day Malaysian Muslim philosopher, concerning the philosophy of happiness. It also focuses on the Aristotelian philosophy of happiness, underscoring the discussion from his seminal book The Nichomachean Ethics, and includes an in-depth study of happiness as discussed by modern Western philosophers like Jeremy Bentham, John Stuart Mill and Immanuel Kant. The study follows a qualitative, non-empirical, textual and contextual analytical approach, which comprises several texts and journal archives composed by the aforementioned scholars and philosophers from the ancient medieval period to the present. The analysis reveals that Islamic philosophy always underscores happiness in this present life and the eternal life after death, while Aristotelian pagan philosophy stresses happiness only in this sublunary life. The study also argues that virtue is a predominant aspect necessary to attain happiness in the worldly life and in the afterlife.